Kesetimbangan Adsorpsi Logam Fe (II) Menggunakan Karbon Aktif Dari Ampas Tebu Sebagai Adsorben - Yenti, Silvia Reni; Yuanita, Mira; Chairul, Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Bagasse is a by-product from pressing liquid sugar. One of the efforts to control the bagasse is processed into activated carbon. This study aims to activated carbon from bagasse, study the effect of Fe (II) concentration on activated carbon from bagasse and adsorption equilibrium model. Processing bagasse into actived carbon carbonization process is carriedout at a temperature of 320 °C for 2 (two) hours. After that activated with KOH ratio 3:1. 2 grams of activated carbon was added to the beaker containing the solution of Fe (II) atvarious concentration (20; 30; and 40 ppm), and the reaction temperature (40; 50; and 60 °C). The results showed that activated carbon adsorption for 20 ppm and 40 °C is 90,80%,followed equilibrium Freundlich and Langmuir isotherm models (with regretion 0,986 and0,985) and the heat of reaction of 2,24 kcal/mol°K.Keywords : adsorption, ion Fe (II), adsorption isotherm, activated carbon